Practical Guide to SAP Transportation Management (TM) - Gotz, Anette; Gotz, Tobias ([California] : CreateSpace Independent Publishing Platform, 2015)
Managing the movement of goods from one place to another is just one small requirement of a Transportation Management (TM) software. To understand the complete process, there is so much more to consider. This guide provides a comprehensive overview of the transportation processes supported by SAP TM 9.3 including functional highlights, system architecture options (including HANA), and integration aspects. Dive into planning, execution, and tracking processes and detailed configuration. Get best practices on how to best set up capacity management functionality and learn more about charge calculation and settlement.
1. End to end transportation processes enabled by SAP Transportation Management including document flow -- 2. SAP TM solution highlights and best practices -- 3. Key innovations with SAP TM 9.2 -- 4. Solution architecture and integration with other SAP components.
Includes index.
Keywords: TRANSPORTATION -- DATA PROCESSING